2019
DOI: 10.3389/fpsyg.2019.01527
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Life Perspectives After War: Evaluation and Adaptation of the Future Expectation Scale in Uganda

Abstract: The formulation of life perspectives is one of the developmental tasks of adolescence. Expectations regarding one’s own future are shaped by cultural and contextual factors. However, there is little cross-cultural research that includes countries affected by war and turmoil. A Ugandan version of the Future Expectations Scale for Adolescents (FESA) was developed and evaluated with a sample of 279 Ugandan adolescents with low socioeconomic status living in rural communities affected by the Ugandan civil war (198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
3
0
2
Order By: Relevance
“…Pooling of the items of the original scale resulted in a different number of items in the adopted version. When designing the questionnaire and conducting studies, paying attention to the item pool is important because of changes in factor structures [ 36 , 37 ]. The authors confirmed that the first version of the questionnaire included 15 questions, but they removed three questions (Items 3, 4, and 14) that did not meet the threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Pooling of the items of the original scale resulted in a different number of items in the adopted version. When designing the questionnaire and conducting studies, paying attention to the item pool is important because of changes in factor structures [ 36 , 37 ]. The authors confirmed that the first version of the questionnaire included 15 questions, but they removed three questions (Items 3, 4, and 14) that did not meet the threshold.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many African women, who have traditionally worked at home, are becoming more educated and taking on new positions in the society, while their traditional role and relationship with men is also evolving in the wake of globalization (Gerland et al, 2017). This phase of transition in Western Africa social space may generate increased risk of bias in the measurement of social functioning (Saupe et al, 2019).…”
Section: Discussion Of What Went "Wrong": Potential Threats To Content Validitymentioning
confidence: 99%
“…Основу дослідження закладена адаптована до пост військової ситуації в країні. Було використано Шкалу майбутніх очікувань (FESA) [9], за допомогою якої вимірювалися очікування дітей та підлітків щодо свого майбутнього у таких сферах як освіта і робота, шлюб та сім'я, церква і суспільство [10].…”
Section: Kunytsia Tetiana Yuryivnaunclassified